1985
DOI: 10.1161/01.res.57.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Vascular prostaglandin and thromboxane production in a canine model of myocardial ischemia.

Abstract: Whereas numerous studies have investigated the role of prostacyclin and thromboxane A2 in the maintenance of coronary blood flow, most of these have focused on normal vessels. In the present investigation, we examined the prostaglandin- and thromboxane-synthesizing capacity of isolated coronary artery segments obtained from the site of a critical coronary artery stenosis. Cyclic flow variations were produced by placing a hard cylindrical constrictor on the proximal left anterior descending coronary artery in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 42 publications
(14 reference statements)
4
33
0
Order By: Relevance
“…Thromboxane A 2 is a potent coronary vasoconstrictor (28) and contributes to the genesis of arrhythmias (29) and cyclical reductions in coronary blood flow (30) in the ischemic myocardium. Hydroxyeicosatetraenoic acid and thromboxane A 2 appear to contribute to the no-reflow phenomenon after reperfusion of previously ischemic myocardium (31).…”
Section: Discussionmentioning
confidence: 99%
“…Thromboxane A 2 is a potent coronary vasoconstrictor (28) and contributes to the genesis of arrhythmias (29) and cyclical reductions in coronary blood flow (30) in the ischemic myocardium. Hydroxyeicosatetraenoic acid and thromboxane A 2 appear to contribute to the no-reflow phenomenon after reperfusion of previously ischemic myocardium (31).…”
Section: Discussionmentioning
confidence: 99%
“…35 Prostacyclin, a key vasodilator and inhibitor of platelet aggregation, is synthesized primarily in endothelial cells that were damaged in this model. There were aggregation of platelets and infiltration of inflammatory cells, both capable of thromboxane synthesis.…”
Section: Dynamic Coronary Obstruction Unstable Angina Pectorismentioning
confidence: 94%
“…There were aggregation of platelets and infiltration of inflammatory cells, both capable of thromboxane synthesis. 35 Serotonin tissue concentrations were also found to be elevated; platelet aggregates were considered to be the source. 36 It was hypothesized that endothelial injury in unstable lesions in humans and in the Folts et al 31 canine model caused attachment and activation of platelets, which in turn release thromboxane and serotonin.…”
Section: Dynamic Coronary Obstruction Unstable Angina Pectorismentioning
confidence: 99%
“…Agents specifically designed to inhibit platelet function, including serotonin receptor antagonists (9-1 1), TXA2 synthesis inhibitors (12) or receptor antagonists (13), or MAbs to the platelet glycoprotein lIb/IlIa receptor (22), prevent the occurrence of CFVs in most cases. Furthermore, histologic examination of coronary arteries obtained at the nadir ofcyclic flow variations consistently reveals an adherent platelet mass (12,14,20 Exercise protocol. After recovery from the surgical procedure was complete and dogs were able to walk comfortably, the effect of treadmill exercise on the development ofcyclic flow variations was tested in 11 dogs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that serotonin (9)(10)(11) and thromboxane A2 (TXA2) (12)(13)(14) are important mediators of coronary occlusion due to platelet aggregation in anesthetized dogs with coronary artery stenoses and endothelial injury. Other factors may be important in governing the process of platelet aggregation at sites of coronary artery stenosis in awake, active animals.…”
Section: Introductionmentioning
confidence: 99%